Brain-derived neurotrophic factor (BDNF) promotes molecular polarization and differentiation of immature neuroblastoma cells into definitive neurons - Hromádková, Lenka; Bezdekova, Dagmar; Pala, Jan; Schedin-Weiss, Sophia; Tjernberg, Lars O; Hoschl, Cyril; Ovsepian, Saak V (Biochimica et biophysica acta. Molecular cell research, 2020)
Throughout development, neuronal progenitors undergo complex transformation into polarized nerve cells, warranting the directional flow of information in the neural grid. The majority of neuronal polarization studies have been carried out on rodent-derived precursor cells, programmed to develop into neurons. Unlike rodent neuronal cells, SH-SY5Y cells derived from human bone marrow present a sub-clone of neuroblastoma line, with their transformation into neuron-like cells showing a range of highly instructive neurobiological characteristics. We applied two-step retinoic acid (RA) and brain-derived neurotrophic factor (BDNF) protocol to monitor the conversion of undifferentiated SH-SY5Y into neuron-like cells with distinctly polarized axon-dendritic morphology and formation of bona fide synaptic connections. We show that BDNF is a key driver and regulator of the expression of axonal marker tau and dendritic microtubule-associated protein-2 (MAP2), with their sorting to distinct cellular compartments. Using selective kinase inhibitors downregulating BDNF-TrkB signaling, we demonstrate that constitutive activation of TrkB receptor is essential for the maintenance of established polarization morphology. Importantly, the proximity ligation assay applied in our preparation demonstrates that differentiating neuron-like cells develop elaborate synaptic connections enriched with hallmark pre- and postsynaptic proteins. Described herein findings highlight several fundamental processes related to neuronal polarization and synaptogenesis in human-derived cells, which are of major relevance to neurobiology and translational neuroscience.
Keywords: Neurogenesis; biologické markery; Cell Line, Tumor; Biomarkers; neurogeneze; buněčná diferenciace; lidé; Reactive Oxygen Species; neurony; signální transdukce; Signal Transduction; Neurons; Brain-Derived Neurotrophic Factor; reaktivní formy kyslíku; Neuroblastoma; mozkový neurotrofický faktor; Cell Differentiation; neuroblastom; nádorové buněčné linie; Humans